PENGARUH CITRA MEREK, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Mahasiswa Manajemen Universitas PGRI Semarang Angkatan 2021) - Slamet Wahyu Aji; Fitri Nur Hidayah; Rauly Sijabat (Jurnal Ekonomi dan Bisnis, 2024)
Many Indonesians themselves tend to follow the world of fashion and accessories. The development of technology and information in Indonesia is increasing, making the development of existing trends. Jims Honey is a local brand operating in the fashion sector. Even though Jims Honey is a local brand, it is still able to compete with other brands. The aim of this research is to determine the influence of brand image, price and product quality on purchasing decisions. The method used is a quantitative approach, while determining the sample uses a non-probability sample. The results of this analysis are not in line with previous research according to Marissa Grace Haque (2020) entitled The Influence of Product Quality and Price on Purchasing Decisions at PT Berlian Multitama in Jakarta, the result of which is that Price (X2) influences consumers to purchase at PT Multitama in Jakarta. Jakarta..The results of hypothesis testing, the value of t calculated > t table is 5.613 > 2.003, which means H2 is accepted..The results of this analysis mean that rising or falling prices do not influence consumers' decisions to buy Jims Honey products..So the better the brand image and product quality, the better Purchasing decisions to buy products from Jims Honey are increasing